Pedagogical competence of Akidah Akhlak teachers in instilling the values of tawhid - Basinun Basinun; Deni Febrini; Ellyana Ellyana; Sri Yuliani (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
The purpose of this study was to describe the pedagogical competence of akidah moral teachers in instilling the values of monotheism in MAN throughout Bengkulu Province and to describe the learning outcomes of students on the material of monotheism values in MAN throughout Bengkulu Province. The descriptive method with a qualitative case study approach is in accordance with this research. The object of research is the pedagogical competence of Akidah Akhlak teachers in instilling the values of monotheism in MAN throughout Bengkulu Province. From the research, it was found that the competence of teachers in instilling the values of monotheism in Akidah Akhlak subjects was influenced by various factors including teacher educational background, learning culture in schools, and support from the school affected the integrity of teachers in teaching.